A simple-to-implement real options method for the energy sector. (15th April 2020) - Locatelli, Giorgio; Mancini, Mauro; Lotti, Giovanni
Abstract: Investment appraisal methods based on real options are gaining popularity in academia, while the adoption by practitioners is still infrequent. Having in mind practitioners, the method is designed to be: conceptually easy to understand, based on realistic hypotheses and data available, able to provide quantitative indications and strategic guidelines. The method is based on a systematic simulation of several scenarios generated according to exercise thresholds of relevant investment parameters. An exercise threshold gives to the investors the exercise right of taking some decision, for instance building a power plant. An exercise threshold is therefore a rule to decide whether to exercise or not a certain option on the basis of the values of one or more state variables. Consequently, the probability distribution of the Net Present Value (or analogous indicator) of the investment is a function of the state variables and the exercise threshold. Systematically changing the exercise thresholds allow to (A) establishing the "real option value" and (B) calculate relevant indications about when and on which type of plant to invest. The method is presented in detail and applied to a case study assessing the investment appraisal of: coal plant, gas plant, large nuclear reactor and small modular reactor. Highlights: Discounted Cash Flow (DCF) is the standard approach for project appraisal. Real Options methods (RO) are appropriated for risky projects. RO methods are difficult to apply for practitioners, therefore they often use the DCF. The paper presents a RO method specifically designed for the practitioners. This approach provides meaningful indicators for decision makers in the energy industry.